2019
DOI: 10.1021/acsnano.9b03288
|View full text |Cite
|
Sign up to set email alerts
|

Amplified Cancer Immunotherapy of a Surface-Engineered Antigenic Microparticle Vaccine by Synergistically Modulating Tumor Microenvironment

Abstract: Efficient cancer vaccines not only require the co-delivery of potent antigens and highly immunostimulatory adjuvants to initiate robust tumor-specific host immune response but also solve the spatiotemporal consistency of host immunity and tumor microenvironment (TME) immunomodulation. Here, we designed a biomaterials-based strategy for converting tumor-derived antigenic microparticles (T-MPs) into a cancer vaccine to meet this conundrum and demonstrated its therapeutic potential in multiple murine tumor models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 46 publications
0
58
0
Order By: Relevance
“…Reprograming TAMs toward the anti‐tumor M1‐like phenotype is another promising strategy. [ 47 ] Many cytokines, immunoagonists, and inhibitors against TAMs (such as IL‐12, [ 48 ] CpG oligonucleotides, [ 49–51 ] TLR agonists, [ 47,52–54 ] and miR‐125b [ 55 ] ) can be used to reprogram TAMs. Huang et al.…”
Section: Engineering Macrophages For Cancer Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Reprograming TAMs toward the anti‐tumor M1‐like phenotype is another promising strategy. [ 47 ] Many cytokines, immunoagonists, and inhibitors against TAMs (such as IL‐12, [ 48 ] CpG oligonucleotides, [ 49–51 ] TLR agonists, [ 47,52–54 ] and miR‐125b [ 55 ] ) can be used to reprogram TAMs. Huang et al.…”
Section: Engineering Macrophages For Cancer Immunotherapymentioning
confidence: 99%
“…[ 59 ] Further, amplified immunotherapy was accomplished by constructing tumor‐derived antigenic microparticles (T‐MPs) loaded with iron oxide nanoparticles and CpG‐containing liposomes, which can convert TAMs to M1 macrophages via nano‐Fe 3 O4 and induce infiltration of cytotoxic T cells. [ 51 ] Similarly, Zhao et al. repolarized TAMs by using ferumoxytol combined or surface‐functionalized with the TLR3 agonist poly(I:C) to promote melanoma regression.…”
Section: Engineering Macrophages For Cancer Immunotherapymentioning
confidence: 99%
“…Nano‐Fe 3 O 4 is encapsulated in T‐MPs to prepare Fe 3 O 4 /T‐MPs, which are tethered with CpG‐loaded liposomes on the surface to generate a vaccine of Fe 3 O 4 /T‐MPs‐CpG/Lipo. This nano‐modified T‐MP vaccine elicits strong antitumor T‐cell immune response by triggering DC antigen cross‐presentation [65]. In addition, studies from the Mooney's group have explored two mechanical approaches (extrusion and sonication, respectively) to produce subcellular vesicles, and they demonstrated that adjuvant (CpG)‐loaded such microvesicles can present tumor antigens to DCs and induce antitumor T‐cell response [66].…”
Section: T‐mps Act As Potential Cancer Vaccinesmentioning
confidence: 99%
“…Besides, immune checkpoint PD-L1 blockade and Lipo/Fe3O4/T-MPsCpG vaccine synergistically enhanced the anti-tumor immunity of mice, significantly prolonging the survival period of mice to 3 months. [93]…”
Section: Nano Vaccinementioning
confidence: 99%
“…The results indicated that the T‐MPS‐CpG/Lipo/Fe3O4 vaccine could transform cold cancer into hot cancer by adjusting the time and space of TME, thereby maximizing the induction of anti‐tumor immunity. Besides, immune checkpoint PD‐L1 blockade and Lipo/Fe3O4/T‐MPsCpG vaccine synergistically enhanced the anti‐tumor immunity of mice, significantly prolonging the survival period of mice to 3 months [93] …”
Section: Combination Of Nanotechnology‐based Immune Checkpoint Blockimentioning
confidence: 99%